A water-soluble pyrazino[2, 3-g]quinoxaline photosensitizer for high-efficiency one- and two-photon excited bioimaging and photodynamic therapy. Issue 41 (16th April 2020) - Zhang, Li-Peng; Li, Xianqiang; Liu, Tianlong; Kang, Lin; Huang, Xing; Zhao, Yuxia
Abstract : A water-soluble pyrazino[2, 3- g ]quinoxaline photosensitizer was synthesized and exhibited excellent performance for both one- and two photon excited bioimaging and photodynamic therapy. Abstract : A water-soluble photosensitizer, PQs-PEG5, based on a novel pyrazino[2, 3- g ]quinoxaline (PQ) prototype compound (PQs-5), was designed and synthesized. It has strong linear absorption within 400–600 nm and a desirable two-photon absorption cross section (100–1290 GM) within 740–1000 nm, and it exhibits both a high fluorescence quantum yield (∼0.55) and singlet oxygen quantum yield (∼0.47). By carrying out in vitro cell imaging and photodynamic therapy (PDT) experiments on PQs-PEG5 with HeLa and 4T1 cells, it was demonstrated that PQs-PEG5 can present outstanding bioimaging performance and PDT efficacies simultaneously. Under one-photon excitation (1PE) of a 635 nm diode laser (60 mW cm −2, 5 min) or two-photon excitation (2PE) of an 820 nm fs laser (100 mW, 80 MHz, 140 fs, 5 min), PQs-PEG5 (10 μM) could cause HeLa and 4T1 cell death effectively, which indicated its great potential as a novel photosensitizer for both 1PE- and 2PE-PDT applications.